Meaningful patient and public engagement in dissemination—embedding co-production in dementia research - de Wolf-Linder, Susanne; Kramer, Iris; Hersperger, Martina; Schubert, Maria; Bächi, Sonja; Stolz, Monika; Wolverson, Emma; Ramsenthaler, Christina (Frontiers in Dementia, 2024)
Patient and Public Involvement and Engagement (PPIE) is still underutilized in both dementia research and corresponding dissemination activities.To describe the methods, format, and lessons learned in co-creating and co-producing a dissemination strategy for a research project focused on establishing patient-centered outcome measures into routine palliative community care for persons living with dementia (PLWD) and their informal carers.A participatory, hybrid-format workshop was conducted to co-create the dissemination strategy with a PPIE group. A video presentation of findings and a list of prompts shared prior to the workshop were used to elicit views on dissemination strategies and knowledge translation. The workshop was followed up with a survey to consolidate the dissemination strategy. Workshop minutes and survey responses were analyzed using qualitative thematic analysis.22 participants from our diverse PPIE group attended the workshop. Two major themes emerged: (a) Knowledge translation: building bridges between research and practice, and (b) Collaboration and dissemination: everyone's voice is needed. Participants suggested critical changes to dissemination methods and materials. Successful knowledge translation depends on a strong evidence base. For this, materials need to be tailored to specific audiences. Everyone's voice needs to be integrated through coproduction in dissemination activities by PPIE members to influence societal change. Tailored dissemination activities within a dissemination strategy were co-created spanning all phases of the research cycle.Informing and educating the public and policymakers about the needs of PWLD relies on disseminating and fostering knowledge translation throughout all phases of the research cycle.